Influence of maternal tobacco smoking during pregnancy on uterine, umbilical and fetal cerebral artery blood flows - Albuquerque, Cheryl A.; Smith, Karen R.; Johnson, Cherie; Chao, Rex; Harding, Richard (Early human development, 2004)
Cigarette smoking during pregnancy is a major cause of adverse perinatal outcome but effects on critical fetal and maternal circulations remain unclear. To determine (1) the influence of habitual maternal cigarette smoking on blood flow velocities in uterine, umbilical and fetal middle cerebral arteries, and (2) the time-course of changes in these flows after smoking a cigarette. In 74 women who smoked and 69 non-smoking controls we measured Doppler blood flow velocity waveforms in the uterine, umbilical and fetal middle cerebral (MCA) arteries; smokers were divided into light (<10 cigarettes/day, n=28) and heavy smokers (>10 cigarettes/day, n=45). In the uterine artery there was no significant difference between the systolic/diastolic (S/D) ratio in smoking and non-smoking women; however, in smokers, a diastolic notch was more frequently observed in the uterine artery waveform than in controls ( p<0.05), suggestive of a greater resistance in the uterine vasculature. In the umbilical artery, the S/D ratio was significantly greater in smokers than in non-smokers. In the fetal MCA, the S/D ratio was higher in heavy smokers than in light smokers ( p<0.05) indicative of greater cerebrovascular resistance. There were no significant correlations between the interval between smoking the last cigarette and making the Doppler measurements and the S/D ratios in any of the vessels. Maternal cigarette smoking is associated with evidence of chronically increased resistances in the uterine, umbilical and fetal middle cerebral arteries.